2015
DOI: 10.1080/00918369.2015.1091207
|View full text |Cite
|
Sign up to set email alerts
|

How Like Perceives Like: Gay People on “Gaydar”

Abstract: When lacking explicit knowledge of someone's sexual orientation, gay people commonly assess the likelihood that another is gay using their "gaydar." The term gaydar is a playful mix of the word gay with radar, suggesting that one can sense, intuit, or perceive some set of characteristics in another that signal a shared minority status. While commonly mentioned, the exact criteria a gay person uses when employing their gaydar are little discussed. Drawing methodologically on a series of five focus groups of sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Hypothesis 2, derived from the assumption that only sexual minorities consciously monitor information about SO in social interaction was not confirmed; instead we found that men believed that their voices are more revealing of their SO than women did. It is possible that stronger stereotypes about gay voice exist for men than women, triggering the belief that men's SO is easier to detect than women's (see Barton, 2015). Beside such gender difference, and in line with Hypothesis 3, sexual majority participants who perceived themselves as sounding gender-conforming and sexual minority participants who perceived themselves as sounding gender-atypical were those who also considered their voices most revealing of their SO.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Hypothesis 2, derived from the assumption that only sexual minorities consciously monitor information about SO in social interaction was not confirmed; instead we found that men believed that their voices are more revealing of their SO than women did. It is possible that stronger stereotypes about gay voice exist for men than women, triggering the belief that men's SO is easier to detect than women's (see Barton, 2015). Beside such gender difference, and in line with Hypothesis 3, sexual majority participants who perceived themselves as sounding gender-conforming and sexual minority participants who perceived themselves as sounding gender-atypical were those who also considered their voices most revealing of their SO.…”
Section: Discussionmentioning
confidence: 85%
“…As in other domains, stereotypes about voices cast gay/lesbian people as gender inverts (Kite & Deaux, 1987). Gay men are assumed to lisp and have soft, high-pitched voices, whilst lesbians are believed to sound 'masculine' and have deep and low-pitched voices (Barton, 2015;Shelp, 2003). Speakers whose voices confirm this gender inversion stereotype features are most likely to be judged to be gay/lesbian by others, regardless of their actual SO (Mack & Munson, 2012;Munson, 2007;Sulpizio et al, 2015).…”
Section: Voice As a Cue Of Sexual Orientationmentioning
confidence: 99%
“…Another type of inclusive/exclusive construct is sexuality, which is meant to include all the aspects of self, character, actions, words and traits that indicate, explicitly or implicitly, one's sexuality. For, as scholars argue, sexuality is a cultural construct attached to and defined by attire and clothing style (see especially Holman 1981;Lurie 1981;Tseelon 1989;Davis 1992;Entwistle 2000;Arvanitidou, Gasouka 2013, 111-115), jewellery, facial expressions, posture, body type, walk or gait, and both the type and frequency of gestures (see especially Fasoli et al 2017Fasoli et al , 1261Fasoli et al -1277also: Dunkle, Francis 1990, 157-167;Gaudio 1994, 30-57;Shelp 2002, 1-14;Munson et al 2006, 202-240;Munson 2007, 125-142); Rieger et al 2010, 124-40;Barton 2015Barton , 1615Barton -1637. It is the interconnection between religion and sexuality as manifested in Attic forensic oratory that this paper aims to explore.…”
Section: Identity: Definition and Constructionsmentioning
confidence: 99%
“…In general, men believed their voices were more revealing than women did. The authors considered this to be a possible indicator of more marked stereotypes in connection with gay voices (see also [50]). Interestingly, masculine-sounding heterosexual men were the ones with the strongest wish to disclose their sexual orientation.…”
Section: Introductionmentioning
confidence: 99%